Contemporary leadership in sport organizations - Scott, David, 1956- (HUMAN KINETICS, 2014)
This text blends research on leadership with practical application of the skills and knowledge that students will need on the job. This text provides sport management students with a comprehensive understanding of the complex topic of leadership in sport through a presentation of foundational and contemporary research, numerous practical examples and analytical exercises, and thought-provoking self-assessments and quotes. More than leadership tips from a sport personality, this book translates classic and contemporary research in leadership into leadership skills and behaviors that are useful in present-day sport settings. Synopses of research findings are presented in table format for an accessible approach to understanding the three Rs of leadership: relationships, results, and responsibility.